(untitled) (Zaporizhzhia Historical Review, 2021)
The article illuminates the financial aspect of Directory UNR and its government politics during the so-called “Kyiv period” of restored UNR, which lasted since the crush of hetman P.Skoropadsky’s regime (December 14, 1918) till the evacuation of Ukrainian government form Kyiv before the city was captured by Bolsheviks (February 5, 1919).